tính đạo hàm của các hàm số sau x^2 +2/can 2x^2+1 26/07/2021 Bởi Mary tính đạo hàm của các hàm số sau x^2 +2/can 2x^2+1
Đáp án: `y = (x^2 + 2)/(\sqrt{2x^2 + 1})` `y’ = ((x^2 + 2)/(\sqrt{2x^2 + 1}))’ = [(x^2 + 2)’\sqrt{2x^2 + 1} – (x^2 + 2)(\sqrt{2x^2 + 1})’]/(2x^2 + 1) = (((x^2)’ + 2′) . \sqrt{2x^2 + 1} – (x^2 + 2). [(2x^2 + 1)’]/[2\sqrt{2x^2 + 1}])/(2x^2 + 1)` `= (2x . \sqrt{2x^2 + 1} – (x^2 + 2) . (2x)/\sqrt{2x^2 + 1})/(2x^2 + 1)` `= (2x(2x^2 + 1) – (x^2 + 2)2x)/[\sqrt{2x^2 + 1}(2x^2 + 1)]` `= (2x^3 – 2x)/[\sqrt{2x^2 + 1}(2x^2 + 1)]` Giải thích các bước giải: Bình luận
$y=\dfrac{x^2+2}{\sqrt{2x^2+1}}$ $y’=\dfrac{2x.\sqrt{2x^2+1}-(x^2+2).\dfrac{2.2x}{2\sqrt{2x^2+1}} }{2x^2+1}$ $=\dfrac{2x\sqrt{2x^2+1}-(x^2+2).\dfrac{2x}{\sqrt{2x^2+1}} }{2x^2+1}$ $=\dfrac{2x(2x^2+1)-2x(x^2+2)}{(2x^2+1).\sqrt{2x^2+1}}$ $=\dfrac{2x(2x^2+1-x^2-2)}{(2x^2+1).\sqrt{2x^2+1}}$ $=\dfrac{2x(x^2-1)}{(2x^2+1)\sqrt{2x^2+1}}$ Bình luận
Đáp án:
`y = (x^2 + 2)/(\sqrt{2x^2 + 1})`
`y’ = ((x^2 + 2)/(\sqrt{2x^2 + 1}))’ = [(x^2 + 2)’\sqrt{2x^2 + 1} – (x^2 + 2)(\sqrt{2x^2 + 1})’]/(2x^2 + 1) = (((x^2)’ + 2′) . \sqrt{2x^2 + 1} – (x^2 + 2). [(2x^2 + 1)’]/[2\sqrt{2x^2 + 1}])/(2x^2 + 1)`
`= (2x . \sqrt{2x^2 + 1} – (x^2 + 2) . (2x)/\sqrt{2x^2 + 1})/(2x^2 + 1)`
`= (2x(2x^2 + 1) – (x^2 + 2)2x)/[\sqrt{2x^2 + 1}(2x^2 + 1)]`
`= (2x^3 – 2x)/[\sqrt{2x^2 + 1}(2x^2 + 1)]`
Giải thích các bước giải:
$y=\dfrac{x^2+2}{\sqrt{2x^2+1}}$
$y’=\dfrac{2x.\sqrt{2x^2+1}-(x^2+2).\dfrac{2.2x}{2\sqrt{2x^2+1}} }{2x^2+1}$
$=\dfrac{2x\sqrt{2x^2+1}-(x^2+2).\dfrac{2x}{\sqrt{2x^2+1}} }{2x^2+1}$
$=\dfrac{2x(2x^2+1)-2x(x^2+2)}{(2x^2+1).\sqrt{2x^2+1}}$
$=\dfrac{2x(2x^2+1-x^2-2)}{(2x^2+1).\sqrt{2x^2+1}}$
$=\dfrac{2x(x^2-1)}{(2x^2+1)\sqrt{2x^2+1}}$